THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL THINK PAIR SHARE (TPS) TO IMPROVE STUDENT LEARNING OUTCOMES ON THE SUBJECT MATTER IN THE CLASSROOM BATTERYMAINTAINS MOTORCYCLE ENGINEERING GRADE X SMK KARSA MULYA PALANGKA RAYA ACADEMIC YEAR 2015/2016 - Dian Tafsirudin; Debora (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The cooperative learning is learning model in which individual achievement has been oriented in group accomplishment. A given method was the learning type of Think pair Share. This is an one of learning model providing the chance to each student for showing the personal participation to others. The technical implement way used is thinking-Cooperating-Sharing. By this model, learning atmosphere would be attractive for students invited to discus in couple term to solve the proposed problems. Learning process is done by giving an opportunity to students for independently thinking and grouping. This research is descriptive type using descriptive method to attempt in describing and interpreting of continuous occurance. Then research subject was using student of X grade motorcycle engineering (TSM) at SMK Karsa Mulya Palangka Raya at academic year 2015/2016 in which there are samples namely 40 students of whole 118 students investigating by simple random sampling method. The data collection was conducted by test, documentation, observation, and questionnaire form. The test result of instrument from 50 multiple choice questions has obtained 33 accepted questions being the instrument in this research. According to TPS achievement grade analysis of learning model implementation on battery maintenance subject for X grade TSM A SMK Karsa Mulya Palangka Raya, it reached 87.50 %. All in all the learning outcomes of students using Cooperative Learning Model-Think Pair Share Type (TPS) is more increase than conventional learning method for X grade TSM A SMK Karsa Mulya Palangka Raya at academic year 2015/2016